(untitled) (Orthodontic Journal of Nepal, 2021)
Clinically, supernumerary teeth are able to cause different local disorders and the most common one is impaction of maxillary incisors. Impacted maxillary incisors substantially affect esthetics, function, and self‑esteem of patients. Impaction of maxillary permanent incisor is a rare clinical entity in dental practice. Although impaction of a permanent tooth is rarely diagnosed during the mixed dentition period, an impacted central incisor is usually diagnosed accurately when there is delay in the eruption of tooth. Multiple treatment options are available for impacted incisors. Surgical-orthodontic treatment is one of the alternative option for the correction. Early diagnosis and management of supernumer¬ary teeth is important to prevent the need for more complex surgical and orthodontic treatment. Here, we present a report of two cases of impacted maxillary incisors and its management